Microplastic pollution of commercial fishes from coastal and offshore waters in southwestern Japan. (January 2022) - Yagi, Mitsuharu; Kobayashi, Tsunefumi; Maruyama, Yutaka; Hoshina, Sota; Masumi, Satoshi; Aizawa, Itaru; Uchida, Jun; Kinoshita, Tsukasa; Yamawaki, Nobuhiro; Aoshima, Takashi; Morii, Yasuhiro; Shimizu, Kenichi
Abstract: Microplastic (MP) pollution in the marine environment is a worldwide issue. There is growing concern of consuming MPs through fish, yet the contamination status of fish collected from deeper waters surrounding Japan remains limited. Here, we presented baseline data on MPs in commercially important fishes from the coastal and offshore waters near Kyushu, Japan (East China Sea). We examined the MPs in the digestive tracts of two pelagic (n = 150) and five demersal species (n = 235). The fish were caught by pole and line, and bottom trawl at different geographical positions. The MPs in pelagic fish (39.1%) were more than in demersal fish (10.3%) and were of larger sizes. Moreover, the MPs correlated with habitat depth and type and species variation in the shape and polymer composition of MPs was observed. The results increase our understanding of the heterogeneous uptake of MPs by fishes. Graphical abstract: Unlabelled Image Highlights: We investigated MPs in commercially important fish species by line and trawling. MPs incidence ranged from 62.5% ( Scomber japonicus ) to 0% ( Lepidotrigla microptera ). The MPs in pelagic fish were more than those in demersal fish and of larger sizes. Film and PE polymer have dominant difference among pelagic and demersal fish.